A game-theoretical model of bank foreign direct investment strategy in emerging market economies. Issue 3 (28th April 2014) - O'Connor, Aidan; J. Santos-Arteaga, Francisco; Tavana, Madjid
Abstract : Purpose: – The purpose of this paper is to propose a game-theoretical model for commercial bank foreign direct investment strategy, government policy and domestic banking industry interactions in emerging market economies and demonstrate the application of this strategy to the banking system. Government policy and domestic banking industry interactions in emerging market economies and demonstrate the application of this strategy to the banking system. Design/methodology/approach: – The paper develops a game-theoretical model to analyze the optimality of the limiting entry strategy followed by a given domestic institutional sector when considering the entry applications of foreign banks in the domestic financial system. The model analyzes the strategic options available to an emerging market country with a relatively underdeveloped banking system when deciding whether or not and to what extent allow for the entrance of better reputed and more technologically advanced foreign banks in its domestic financial system. Findings: – The paper shows that the progressive liberalization of entry restrictions would define the perfect Bayesian equilibria of the subsequent set of continuation games and the respective payoffs derived from this liberalization as the domestic economy integrates and competes within the global financial system. Originality/value: – Banks operating in the international financial market have incentives to invest directly in emerging market economies and governments have incentives in allowing foreign banks entry to their market. As banking systems in these economies are generally underdeveloped, opening the financial system to foreign competitors could lead to a decrease in the market share of local banks. Eventually foreign banks could control the banking system and could de facto control the money supply.